2020
DOI: 10.1093/schbul/sbaa030.520
|View full text |Cite
|
Sign up to set email alerts
|

M208. Measures of Cognition and Social Functioning in Schizophrenia Patients Receiving Sep-363856

Abstract: Background SEP-363856 is a novel trace amine associated receptor-1 (TAAR1)/5-HT1A agonist with no dopamine-D2/5-HT2A antagonist activity. SEP-363856 showed significant antipsychotic efficacy in patients with schizophrenia, and a safety and tolerability profile similar to placebo and consistent with a non-D2 mechanism of action. Here, we examined measures of cognition and social functioning in schizophrenia patients receiving SEP-363856. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…9). 23,24 The extension study also confirmed the effect of ulotaront on negative symptoms: significant improvements from baseline were noted using the PANSS negative subscale, Brief Negative Symptom Scale (BNSS) total score, and uncorrelated PANSS score matrix Negative Apathy/Avolition Factor and Negative-Deficit of Expression Factor scores 23 …”
Section: The New Biology Of Taar1 Agonists: Emerging Agents For the T...mentioning
confidence: 74%
See 4 more Smart Citations
“…9). 23,24 The extension study also confirmed the effect of ulotaront on negative symptoms: significant improvements from baseline were noted using the PANSS negative subscale, Brief Negative Symptom Scale (BNSS) total score, and uncorrelated PANSS score matrix Negative Apathy/Avolition Factor and Negative-Deficit of Expression Factor scores 23 …”
Section: The New Biology Of Taar1 Agonists: Emerging Agents For the T...mentioning
confidence: 74%
“…There is reason to be optimistic that patients with schizophrenia may soon have a truly novel treatment option. Based on the clinical trial data for ulotaront, [22][23][24] it seems TAAR1 agonists have the potential to be both tolerable and effective, including for ameliorating negative and cognitive symptoms. Other emerging therapies include agents targeting muscarinic receptors, oral glycine transporter-1 inhibitors, and medications blocking serotonin 5-HT 2A receptors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations